Aortic root remodelling in competitive athletes. (September 2020) - Abulí, Marc; Grazioli, Gonzalo; Sanz de la Garza, Maria; Montserrat, Silvia; Vidal, Bàrbara; Doltra, Adelina; Sarquella-Brugada, Georgia; Bellver, Montserrat; Pi, Ramon; Brotons, Daniel; Oxborough, David; Sitges, Marta
Background: Controversy remains about the cut-off limits for detecting aortic dilatation in athletes, particularly in large-sized individuals. The allometric scaling model has been used to obtain size-independent measurements in cardiovascular structures in the general population. Aim: The purpose of this study was to validate the use of allometric scaling in the measurement of the aortic root for competitive athletes and to offer reference values. Methods: This was a cross-sectional study that analyses the dimensions of aortic root found in the echocardiogram performed as part of pre-participation sports screening in competitive athletes between 2012–2015. Beta exponents were calculated for height and body surface area in the whole cohort. In order to establish whether a common exponent could be used in both genders the following model was assessed y = a x b*exp(c*sex). If a common exponent could not be applied then sex-specific beta exponents were calculated. Results: Two thousand and eighty-three athletes (64% men) were included, from a broad spectrum of 44 different sports disciplines, including basketball, volleyball and handball. The mean age was 18.2 ± 5.1 years (range 12–35 years) and all athletes were Caucasian, with a training load of 12.5 ± 5.4 h per week. Indexed aortic root dimension showed a correlation with ratiometric scaling by body surface area (r: −0.419) and generated size independence values with a very light correlation with height (r: −0.084); and with the allometric scaling by body surface area (r: −0.063) and height (r: −0.070). The absolute value of aortic root was higher in men than in women ( p < 0.001). These differences were maintained with allometric scaling. Conclusion: Size-independent aortic root dimension values are provided using allometric scaling by body surface area and height in a large cohort of competitive athletes. Aortic root values were larger in men than in women, both in absolute values and after allometric scaling. The use of these indexed aortic reference ranges can be useful for the early detection of aortic pathologies.